Organocatalytic route to the enantioselective synthesis of syn/ anti-α-hydrazino-γ-fluoro alcohols - Khonde, Nilesh S.; Said, Madhukar S.; Danve, Shivam S.; Kumar, Pradeep (Tetrahedron Letters, 2024)
A general organocatalytic method has been developed for the asymmetric synthesis of alpha-hydrazino-gamma-fluoro alcohols, a precursor to syn/anti-1,3-fluoro amines. The strategy employs alpha-fluorination catalyzed by prolinederived catalyst, (S)-alpha,alpha-bis[3,5-bis(trifluoromethyl)phenyl]-2-pyrrolidinemetha nol trimethylsilyl ether followed by Horner-Wadsworth-Emmons (HWE) olefination of aldehydes, and proline-catalyzed alpha-amination as the key steps. The title compounds showed excellent diastereoselectivity (up to 99:1) and enantioselectivity (up to 99 %).
Keywords: alpha-Amination; alpha-Fluorination; diastereoselectivity; Enantioselectivity; HWE olefination; organocatalyst